Keberadaan trading house terhadap pemberdayaan perusahaan industri lokal: studi pada kawasan regional pasca integrasi MEA 2025 - Muljanto Siladjaja; Johannes Ferry Cahya; Sri Yanthy Yosepha; Herni Pujiati (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines how trading houses empower local firms to overcome export barriers, including foreign exchange risks and financing constraints, and serve as mediators that provide crucial market intelligence and quality assurance to reduce business risks. Using Structural Equation Modeling and Focus Group Discussions with 300 stakeholders across Jakarta, Bandung, Semarang, and Surabaya, the research reveals that trading houses significantly enhance export capabilities and support green product development through advanced manufacturing technologies and value-added investments, creating competitive advantages for the ASEAN Economic Community 2025. The findings demonstrate that while these partnerships foster sustainable industrial growth, their effectiveness is hampered by inconsistent national regulations regarding taxation, fees, and green product standards, highlighting the urgent need for more coherent policy frameworks to maximize trading houses' contribution to Indonesia's export development and sustainable manufacturing transition.